Associative mechanisms involved in specific Pavlovian-to-instrumental transfer (PIT) in human learning tasks - Alarcón, Daniel; Bonardi, Charlotte; Delamater, Andrew (SAGE, 2018)
Four experiments compared the effect of forward and backward conditioning procedures on the ability of conditioned stimuli (CSs) to elevate instrumental responding in a Pavlovian-to-instrumental transfer (PIT) task. Two responses were each trained with one distinct outcome (R1->O1, R2->O2), either concurrently (Experiment 1) or separately (Experiments 2, 3 and 4). Then, in Experiments 1 and 2, four CSs were either followed or preceded by one outcome (A->O1, B->O2, O1->C, O2->D). In Experiment 3 each CS was preceded and followed by an outcome: for one group of participants both outcomes were identical (e.g., O1->A->O1, O2->B->O2), but for the other they were different (e.g., O1->A->O2, O2->B->O1). In Experiment 4 two CSs were preceded and followed by identical outcomes, and two CSs by different outcomes. In the PIT tests participants performed R1 and R2 in the presence and absence of the CSs. In Experiments 1 and 2 only the CSs followed by outcomes in Pavlovian training elevated responding. In Experiments 3 and 4 all the CSs elevated responding but based on the outcome that followed them in training. These results support the stimulusoutcome-response (S-O-R) mechanism of specific PIT, according to which CSs elevate responding via activation of its associated outcome representation.